Psikoedukasi pada Pasien Ulkus Diabetik di Rumah Sakit X - Okta Mariana Br Panjaitan; Maria Susila Sumartiningsih; Rima Berlian Putri; Roza Indra Yeni (Jurnal Kesmas Asclepius, 2026)
This study aims to determine the description of psychoeducation in diabetic ulcer patients. The research design uses a quantitative approach. The population in this study were all diabetic ulcer patients undergoing treatment, with a population and sample of 30 respondents. The research instrument used a psychoeducation questionnaire that had been tested for its feasibility. Data analysis was carried out univariately to describe the frequency distribution, mean value, and standard deviation. The results showed that the majority of diabetic ulcer patients were in the moderate psychoeducation category, namely 17 respondents (56.7%), while the low category was 6 respondents (20.0%) and the high category was 7 respondents (23.3%). The average psychoeducation score was 7.99 with a standard deviation of 0.871, which indicates that the level of psychoeducation of respondents was relatively homogeneous. In conclusion, the majority of diabetic ulcer patients have a moderate level of psychoeducation, so structured and ongoing efforts to improve psychoeducation are still needed to achieve a high level. Keywords: Diabetic Ulcers, Patients, Psychoeducation.